Respuesta :

Answer:

5

Step-by-step explanation:

Let's just pretend the 6 numbers are: a,b,c,d,e,f.

Then (a+b+c+d+e+f)/6 =4 (given by first statement.)

Let's pretend the average of 2 numbers is 2 means they are talking about the a and b.

So (a+b)/2=2.

Now we want to find (c+d+e+f)/4 as requested by their question.

So first step multiply both sides of our first equation by 6 giving us:

a+b+c+d+e+f=24

So the second step multiply both sides of our second equation by 2 giving us:

a+b=4.

Now if a+b+c+d+e+f=24 and a+b=4, then c+d+e+f=20 since 20+4=24.

So the average of the four numbers c,d,e, and f is 20/4=5.